The Reasons, the Success and the Strategies of Siam in Annexing Ubon Ratchatani during 1882-1933 - Chotanan, Patawee (Governance Journal, Kalasin University, 2018)
There are two important factors which made Siam annex the area from Korat Plateau to the left side of Maekhong the river. The first factor is an external factor which was the colonization of the western empires, such as the British and French empires influencing in the South East Asia during the nineteenth century. The second factor is an internal factor within Siam. Chulalongkorn, the fifth king of Siam needed to centralize power from his nobles and needed resources from other cities so that Siam would become wealthy and stable. This policy had a significant impact on the cities especially within Ubon Ratchatani which was one of the big and powerful cities in the area. The Ubon Ratchatani king’s power and his status were significantly decreased by Siam. His traditional governing systems, such as governing, collecting taxes and controlling manpower were changed in order to become the same system as Siam. Moreover, the local traditions and cultures of Ubon Ratchatani was changing and substituted by those of Siam in terms of region , education, language, and rituals and traditions. Key Words: Strategies; Annexation; Ubon Ratchatani; Siam